Examination of the relationship between emotional regulation strategies of 5-year-old children and their peer relationships - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
The primary objective of this study is to determine the predictive effect of emotional regulation strategies of 5-year-old children on their peer relationships. The sample group of the study consisted of 95 children aged 5 years (49 (51.6%) girls; 46 (48.4%) boys) receiving education at kindergartens in Turkey. The data required for the study were obtained from children and teachers. 'The Scale of Emotion Regulation Strategies', 'The Social Skills Evaluation Scale', 'The Picture Sociometry Scale', 'Child Behaviour Scale', and 'The Personal Information Form' were used. The results revealed that the emotional regulation strategies had predictive effects on the levels of coping with peer pressure, aggressiveness, and social preference.
Keywords: Emotional regulation strategies; social status; peer pressure; aggressiveness; young children; SOCIAL-STATUS; EARLY-CHILDHOOD; BEHAVIOR; PSYCHOPATHOLOGY; ANTECEDENTS; COMPETENCE